2023
DOI: 10.3233/jad-230104
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Functional and Structural Neural Indices: Potential Biomarkers for the Monitoring of Cerebral Neurodegeneration: The Maastricht Study

Abstract: Background: If retinal indices of neurodegeneration are to be biomarkers for the monitoring of cerebral neurodegeneration, it is important to establish whether potentially modifiable risk factors for dementia are associated with retinal neurodegenerative changes. Objective: To study associations of dementia risk factors with retinal sensitivity, an index of retinal neural function, and retinal nerve fiber layer (RNFL) thickness, an index of retinal neural structure. Methods: We used cross-sectional data from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“… 44 Also in support of this concept, we additionally found that retinal neurodegeneration and cerebral neurodegeneration have shared risk factors. 45 , 46 We recently showed in The Maastricht Study, using data from up to ∼5600 individuals, that most risk factors for dementia, including hyperglycemia and hypertension, were associated with retinal neurodegeneration, as quantified from lower RNFL thickness and worse retinal sensitivity. 45 , 46 Of note, however, as we found relatively weak associations of retinal neuronal variables with brain variables, retinal neuronal imaging biomarkers may by themselves (as singular biomarkers) not be sufficiently informative to use in a clinical care setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 Also in support of this concept, we additionally found that retinal neurodegeneration and cerebral neurodegeneration have shared risk factors. 45 , 46 We recently showed in The Maastricht Study, using data from up to ∼5600 individuals, that most risk factors for dementia, including hyperglycemia and hypertension, were associated with retinal neurodegeneration, as quantified from lower RNFL thickness and worse retinal sensitivity. 45 , 46 Of note, however, as we found relatively weak associations of retinal neuronal variables with brain variables, retinal neuronal imaging biomarkers may by themselves (as singular biomarkers) not be sufficiently informative to use in a clinical care setting.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 We recently showed in The Maastricht Study, using data from up to ∼5600 individuals, that most risk factors for dementia, including hyperglycemia and hypertension, were associated with retinal neurodegeneration, as quantified from lower RNFL thickness and worse retinal sensitivity. 45 , 46 Of note, however, as we found relatively weak associations of retinal neuronal variables with brain variables, retinal neuronal imaging biomarkers may by themselves (as singular biomarkers) not be sufficiently informative to use in a clinical care setting. Future studies should aim to evaluate the added value of retinal imaging biomarkers on top of (a combination of) other non‐invasive and scalable biomarkers for dementia (such as blood‐based biomarkers for amyloid beta and tau in Alzheimer's disease).…”
Section: Discussionmentioning
confidence: 99%